Photovoice: A Novel Approach to Improving Antituberculosis Treatment Adherence in Pune, India. (7th October 2014) - Shelke, Sangita C.; Adhav, Prakash S.; Moonan, Patrick K.; Willis, Matthew; Parande, Malan A.; Satyanarayana, Srinath; Kshirsagar, Vikas D.; Ghosh, Smita
Abstract : We compared antituberculosis treatment (ATT) adherence and outcomes among patients exposed to Photovoice (video of previously cured TB patients sharing experiences about TB treatment) versus those not exposed. The odds of successful outcome (i.e., cured or completing treatment) for the 135 patients who watched Photovoice were 3 times greater (odds ratio: 2.8; 95% CI: 1.3–6.1) than for patients who did not watch Photovoice. The comparison group, on average, missed more doses (10.9 doses; 95% CI: 6.6–11.1) than the intervention group who saw Photovoice (5.5 doses; 95% CI: 3.7–6.1). Using Photovoice at initiation of ATT has the potential to improve treatment adherence and outcomes.